2016
DOI: 10.1111/joca.12082
|View full text |Cite
|
Sign up to set email alerts
|

Brand Iconicity vs. Anti‐Consumption Well‐Being Concerns: The Nutella Palm Oil Conflict

Abstract: This article analyzes how an iconic brand is threatened by the societal trend of anti‐consumption motivated by well‐being. Under scrutiny is the iconic brand Nutella that is recognized worldwide. In France, it has been linked to public debates on well‐being concerns about palm oil. Approaching the phenomenon from a consumer perspective and through observational netnography, we investigate the accommodation work undertaken by Nutella lovers in reaction to anti‐palm oil attacks. We identify three major accommoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 27 publications
1
54
0
3
Order By: Relevance
“…With very few exceptions (Wong et al, 2018), this research focuses on negative emotions and behavior against products and services that consumers express as independent individuals and as members of a collective separately. From the brand management perspective, the different themes share a concern about the harmful potential of anti-brand emotions and behaviors and studies emphasize negative consequences including consumer revenge (Hegner et al, 2017), brand sabotage (Grégoire et al, 2009) or loss of brand strength (Cova & D'Antone, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With very few exceptions (Wong et al, 2018), this research focuses on negative emotions and behavior against products and services that consumers express as independent individuals and as members of a collective separately. From the brand management perspective, the different themes share a concern about the harmful potential of anti-brand emotions and behaviors and studies emphasize negative consequences including consumer revenge (Hegner et al, 2017), brand sabotage (Grégoire et al, 2009) or loss of brand strength (Cova & D'Antone, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Participation in antibrand communities stems from individual affects and behaviors and the link between the two seems to explain the widespread engagement of consumers in collective actions and the seemingly growing importance of these movements (Veloutsou & Guzmán, 2017). Past studies have shown how detrimental strong negativity in the form of brand hate can be (Kähr et al, 2016), calling for a better understanding of collective negativity towards brands and its causes (Cova & D'Antone, 2016). Since brand negativity is detrimental to the brand (Alba & Lutz, 2013), it seems imperative to understand how strong negative feelings move from affecting consumers as individuals acting independently to joining others and developing collective behavior (Bryson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Continuing our focus on the anti‐consumption of brands, in the paper “Brand Iconicity vs. Anti‐Consumption Well‐Being Concerns: The Nutella Palm Oil Conflict,” Cova and D'Antone () look at how brand lovers deal with anti‐consumption activities that may surround their favorite brands. Utilizing an observational netnographic approach across three years of online data, including multiple newspaper articles, blogs, forums, discussion groups, and social networking sites, the authors explore consumer narratives about the moral conflict encircling Nutella.…”
Section: The Papersmentioning
confidence: 99%
“…It is the very first, to the best of our knowledge, to explore how that affects observers' perceptions of brand equity. Our findings can be extremely valuable, given that the creation of brand-related parodies and the expression of negativity toward brands together represent a current and developing trend in co-creation (Cova and D'Antone, 2016;Fournier and Alvarez, 2013;Veloutsou and Guzman, 2017). Our study shows that co-creation which goes wrong is strongly driven by risk affecting brands in general and high-equity brands in particular.…”
Section: Resultsmentioning
confidence: 69%
“…Although such brand parodies and negativity toward brands are a current and developing phenomenon (Fournier and Alvarez, 2013;Rauschnabel et al, 2016;Veloutsou and Guzman, 2017), research has so far paid very little attention to the brand-related effects of non-collaborative co-creation. Non-collaborative behaviour has been identified, however, as a significant feature of interactions between a brand owner and its stakeholders (Echeverri and Skalen, 2011;Gebauer et al, 2013;Greer, 2015) with the attendant danger that altered brand meanings can start to compete with those initially created by brand managers and thereby decrease the value of hitherto successful and competitive brands (Cova and D'Antone, 2016;Giesler, 2012;Thompson et al, 2006). In such a situation, co-creation is not a process of mutual brand-value development, but becomes one of brand-meaning destruction (Gyrd-Jones and Kornum, 2013).…”
Section: Introductionmentioning
confidence: 99%